KEKAYAAN JENIS BURUNG DI PULAU SERANGAN, BALI - SUMARDIKA, I PUTU AGUS; GINANTRA, I KETUT; SUASKARA, I.B. MADE (Jurnal Biologi Udayana; Vol 21 No 2 (2017): JURNAL BIOLOGI UDAYANA, 2017)
This study aims to determine the species richness of bird species on the island of Serangan, Bali in February and March 2016. Observations were made of 20 time, which is held in the morning (06.00-09.00 am) and afternoon (15.00-18.00 pm). Observations were made on five types of habitat that are beaches, mangroves, lagoons, forest plantations and settlements. The study was conducted by recording ten species methods. Identification of species of birds refers to the morphological characters of the and also by voice. The results showed 55 species of birds are found in five types of habitat which is included in 30 families, 25 types of which are species of shore birds and 30 species are terrestrial birds. In the lagoon habitat found 46 species, on mangrove found 28 species, forest plants are found 22 species, Beach habitat are found 20 species and settlements are found 14 species of birds. Similarity index of bird species in each habitat were: the beachmangrove 63%, beach-lagoon 61%, coast-forest plants 48%, beach-residential 47%, mangrove-lagoon 68%, mangrove-forest plants 52%, mangrove-residential 48%, the lagoon-forest plants 47%, the lagoon-residential 40%, plantations-residential 56%. Of the 55 species of birds were found, 15 species are protected birds and 12 species are migratory birds.